1858-1859 N.M. Laws 68, ch. 26, § 7 - (:unkn) unknown (My University, 1858)
Prohibited any person to transfer to "any slave any sword, dirk, bowie-knife, gun, pistol or other fire arms, or any other kind of deadly weapon of offence, or any ammunition of any kind suitable for fire arms."
Keywords: ENSLAVED PERSONS & OTHER MINORITIES